The Prevalence, Correlates and Functions of Non-Suicidal Self-Injury in Vietnamese Adolescents - Thai TT (Dove Medical Press, 2021)
Truc Thanh Thai,1 Mairwen K Jones,2 Thao Phuong Nguyen,1 Thao Van Pham,1 Han Hy Thi Bui,3 Loan Xuan Kim,1 Tap Van Nguyen4 1Faculty of Public Health, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City Vietnam; 2Faculty of Medicine & Health, The University of Sydney, Sydney, New South Wales, Australia; 3Woolcock Institute of Medical Research Vietnam, Ho Chi Minh City, Vietnam; 4Department of Medicine and Pharmacy, Tra Vinh University, Tra Vinh, VietnamCorrespondence: Truc Thanh ThaiFaculty of Public Health, University of Medicine and Pharmacy at Ho Chi Minh City, Ho Chi Minh City, VietnamTel +84 908381266Email thaithanhtruc@ump.edu.vnTap Van NguyenDepartment of Medicine and Pharmacy, Tra Vinh University, Tra Vinh, VietnamTel +84 914064340Email nvtap@tvu.edu.vnPurpose: Research conducted across different countries has consistently identified non-suicidal self-injury (NSSI) to be a common and significant public health problem. This study examined the prevalence, associated factors and functions of NSSI, among a large sample of Vietnamese adolescents.Methods: A total of 1316 high school students (15– 18 years old, 63.3% female) across urban and suburban areas in Ho Chi Minh City, participated in this cross-sectional study. NSSI was assessed by the Functional Assessment of Self-Mutilation.Results: Almost half (43.9%) of the adolescents engaged in at least one type of NSSI within the preceding 12-month period and more than one quarter (26.1%) engaged in multiple types of NSSI. Hitting self on purpose (23.1%), picking at a wound (17.0%), or biting self (16.7%) were the most frequent behaviours. Severe forms of NSSI such as scraping, burning or erasing skin were reported by 17.2%. The most common functions for NSSI were to stop bad feelings (56.0%), to punish self (48.7%), to get control of a situation (44.0%) and to feel relaxed (42.2%). Symptoms of depression, anxiety and stress were significant factors associated with NSSI, particularly for participants who engaged in moderate/severe NSSI and multiple types of NSSI.Conclusion: High rates of NSSI were found in Vietnamese adolescents. There is a pressing need for the development and implementation of effective interventions to reduce NSSI. Strategies that promote positive mental health and reduce symptoms of depression, anxiety and stress as well as approaches that help adolescents manage their internal emotions are likely to be beneficial.Keywords: non-suicidal self-injury, functions, high school students, adolescents, associated factors, Vietnam